Effectiveness of a Time-limited Incentive on Participation by Hard-to-reach Respondents in a Panel Study. Issue 3 (August 2017) - Fomby, Paula; Sastry, Narayan; McGonagle, Katherine A.
We describe an experiment to provide a time-limited incentive among a random sample of 594 hard-to-reach respondents, 200 of whom were offered the incentive to complete all survey components of a study during a three-week winter holiday period. Sample members were primary caregivers of children included in the 2014 Child Development Supplement to the U.S. Panel Study of Income Dynamics. The incentive provided US$50 to caregivers who completed a 75-minute telephone interview and whose eligible children each completed a 30-minute interview. Results indicate that the incentive was an effective and cost-efficient strategy to increase short-term response rates with hard-to-reach respondents and had no negative impact on final response rates.